Interpersonal relationships and creativity at work: A network building perspective. Issue 3 (31st May 2021) - Ozer, Muammer; Zhang, Guangxi
Abstract: The important role of social networks in creativity has long been recognized in the literature. However, research to date has primarily focused on the structural, informational, and relational dimensions of social networks in creativity. Acknowledging the importance of employees themselves, past research has also called for further research to study the human side of social networks in addition to their structural, informational, and relational dimensions. Addressing this research need, we studied the indirect relationship between employees' tertius iungens orientation (i.e., their strategic, purposeful, and effortful behavior to either connect otherwise disconnected coworkers in their organization or facilitate preexisting relationships among them) and their creativity through their interpersonal relationships with their coworkers. In addition, we studied how this indirect relationship is moderated by the expectations of both the focal employees and their coworkers. Based on a multi‐source and multi‐wave survey study in one of the major Internet companies in the world, our results showed that employees with a tertius iungens orientation enjoyed high‐quality interpersonal relationships with their coworkers and in turn exhibited high levels of creativity. The results also indicated that while employees' job aspirations positively moderated the relationship between their tertius iungens orientation and interpersonal relationships, their organizational status positively moderated the relationship between their interpersonal relationships and creativity. These results expand extant research in the area by showing how and under what conditions employees' creativity is influenced by their strategic, purposeful, and effortful behaviors to take advantage of the benefits of social networks. Considering firms' interest and efforts to increase employee creativity, our study also suggests that firms can increase employee creativity by hiring people with a strong tertius iungens orientation and training their existing employees about the value of such an orientation.